Soil organic matter quality and microbial catabolic functions along a gradient of wildfire history in a Mediterranean ecosystem (Applied Soil Ecology, 2011)
The principal aim of this research was to determine the inﬂuence of an increasing wildﬁre history on the recovery at short and long term of soil organic matter (SOM) composition and microbial properties. The contemporary wildﬁre events (since 1950) were recorded for 27 plots located on the siliceous part of the French Mediterranean region (Maures mountain ranges). A wildﬁre history index was built, tested and calculated in order to display numerical values representative of the different wildﬁre history parameters (i.e. number of ﬁres, time since ﬁre and mean ﬁre interval). Microbial basal respiration and biomass were analysed as well as intensity of the use of 31 C-substrates, catabolic diversity and C-substrates utilisation proﬁles. Furthermore, a qualitative characterisation of the SOM was carried out by solid state 13 C NMR. Potential drivers of the microbial recovery were identiﬁed by studying the relationships between microbial activities and chemical functions of SOM. Our results showed that ﬁre histories resulting in considerable losses or alterations of SOM, such as recent or close ﬁres, decreased the microbial catabolic evenness. This could be attributed to a preferential utilisation of N-containing compounds and complex substrates such as aromatic and polymers reﬂecting a greater N microbial demand and a selection of speciﬁc catabolic functions. Moreover, a large number of ﬁres (4 ﬁres in 57 years compared to 1–2) resulted in lasting degradation of the relative intensity of methyl C function in polymethylene, O-Alkyl C, aromatic C and phenolic C functions inducing a slow-down in recovery of microbial properties. These results also conﬁrm our hypothesis that some chemical functions of SOM can be in equilibrium with wildﬁre history. Finally, this research demonstrates that FT-NIR analysis can be used as a valuable tool to assess both the wildﬁre history and the vulnerability of soil quality to shifts in historical ﬁre regimes